2007
DOI: 10.1177/1532673x07304263
|View full text |Cite
|
Sign up to set email alerts
|

Redistricting and Party Polarization in the U.S. House of Representatives

Abstract: The elevated levels of party polarization observed in the contemporary Congress have been attributed to a variety of factors. One of the more commonly recurring themes among observers of congressional politics is that changes in district boundaries resulting from the redistricting process are a root cause. Using a new data set linking congressional districts from 1962 to 2002, we offer a direct test of this claim. Our results show that although there is an overall trend of increasing polarization, districts th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(63 citation statements)
references
References 25 publications
0
62
0
1
Order By: Relevance
“…Um dos trabalhos seminais na literatura foi o desenvolvido por Poole e Rosenthal (1997). Contrariando a consolidada ideia de que os interesses locais do eleitorado dos congressistas norte-americanos é a influência dominante na formação das preferências dos mesmos (ver Mayhew, 1974e Fiorina, 1974 (Carson, Crespin, Ficocchiaro and Rohde, 2007).…”
Section: Dimensionalidade Da Política E Nível De Conflito Interpartidunclassified
“…Um dos trabalhos seminais na literatura foi o desenvolvido por Poole e Rosenthal (1997). Contrariando a consolidada ideia de que os interesses locais do eleitorado dos congressistas norte-americanos é a influência dominante na formação das preferências dos mesmos (ver Mayhew, 1974e Fiorina, 1974 (Carson, Crespin, Ficocchiaro and Rohde, 2007).…”
Section: Dimensionalidade Da Política E Nível De Conflito Interpartidunclassified
“…Noting that polarization levels have been higher in the House, which can be gerrymandered, compared to the Senate which is ungerrymanderable, Carson et al found that congressional districts which have been significantly altered due to the redistricting process tend to be more extreme even after controlling for how safe the seat is and electoral replacement rates (Carson, Crespin, Finocchiaro, & Rohde, 2007). However, some of what might be captured in measuring the effects of gerrymandering could actually be a result of Americans following a trend of living near other like-minded partisans (Bishop, 2008).…”
Section: Redistricting and Polarizationmentioning
confidence: 99%
“…Both strategies are criticized as being unfair to voters because they lead to uncompetitive districts, in which voters in the partisan minority have little opportunity to elect a representative who shares their policy preferences. Moreover, uncompetitive districts may contribute to political polarization by increasing the likelihood that ideologically extreme candidates will be elected (Carson, Crespin, Finocchiaro, and Rohde 2007; but see McCarty, Poole, and Rosenthal 2009). …”
Section: The Redistricting Process and Political Motivationsmentioning
confidence: 99%